Integrasi Computational Thinking Menggunakan Lego Robotika Pada Pembelajaran Pemrograman - Budiyanto, Cucuk Wawan; Amri, Saehful; Yuana, Rosihan Ari; Widiastuti, Indah; Harjunowibowo, Dewanto (DEDIKASI: Community Service Reports, 2023)
School extracurricular activities potentially facilitate the development of students' talents and interests. This community service activity introduces the integration of Lego Mindstorm EV3 Robotics into extracurricular programming activities at PPQ IT Al Mahir, Karanganyar. It is expected to benefit students' Computational Thinking skills and interest in STEM careers of the PPQ-IT Al Mahir Islamic Boarding School students Karanganyar. This community service aimed to develop the character of the Pancasila Student profile according to the purpose of the Merdeka Curriculum. The activity was carried out in the period from July to October 2022. The three stages of community service were 1) preparation, 2) robotics workshop, and 3) deployment. The report concludes that the robotics module ran well for the high-school student level and contributed to the participants' robotics and programming interest. The extracurricular framework would be the potential for deployment in the other school setting.